Temperature‐Reliable Low‐Dimensional Perovskites Passivated Black‐Phase CsPbI3 toward Stable and Efficient Photovoltaics. Issue 23 (5th April 2022) - Tan, Shan; Yu, Bingcheng; Cui, Yuqi; Meng, Fanqi; Huang, Chunjie; Li, Yiming; Chen, Zijing; Wu, Huijue; Shi, Jiangjian; Luo, Yanhong; Li, Dongmei; Meng, Qingbo
Abstract: Low‐dimensional (LD) perovskites can effectively passivate and stabilize 3D perovskites for high‐performance perovskite solar cells (PSCs). Regards CsPbI3 ‐based PSCs, the influence of high‐temperature annealing on the LD perovskite passivation effect has to be taken into account due to fact the black‐phase CsPbI3 crystallization requires high‐temperature treatment, however, which has been rarely concerned so far. Here, the thermal stability of LD perovskites based on three hydrophobic organic ammonium salts and their passivation effect toward CsPbI3 and the whole device performance, have been investigated. It is found that, phenyltrimethylammonium iodide (PTAI) and its corresponding LD perovskites exhibit excellent thermal stability. Further investigation reveals that PTAI‐based LD perovskites are mainly distributed at grain boundaries, which not only enhances the phase stability of CsPbI3 but also effectively suppresses non‐radiative recombination. As a consequence, the champion PSC device based on CsPbI3 exhibits a record efficiency of 21.0 % with high stability. Abstract : Temperature‐reliable low‐dimensional (LD) perovskites (1D PTAPbI3 and 2D PTA2 PbI4 ) are demonstrated to form in situ at grain boundaries and surfaces of CsPbI3 perovskite. As‐formed LD perovskites can effectively passivate the defects in CsPbI3 films and prevent moisture intrusion as well. This PTAI‐based LD‐decorated CsPbI3 perovskite solar cell exhibits a record efficiency of 21.0 % with enhanced stabilities.